Macromolecular array patterns of silk gland secretion in social Hymenoptera larvae - Gomes, Guilherme [UNESP]; Silva-Zacarin, Elaine C.M. [UNESP]; Zara, Fernando J. [UNESP]; Silva de Moraes, Regina L.M. [UNESP]; Caetano, Flávio H. [UNESP] (My University, 2004)
The cocoon, produced by most holometabolous insects, is built with silk that is usually produced by the larval salivary gland. Although this silk has been widely studied in the Lepidoptera, its composition and macromolecular arrangement remains unknown in the Hymenoptera. The macromolecular array patterns of the silk in the larval salivary gland of some meliponids, wasps, and ants were analyzed with polarized-light microscopy, and they were compared with those of Bombyx mori (Lepidoptera). There is a birefringent secretion in the glandular lumen of all larvae, due to filamentous structural proteins that display anisotropy. The silk in the distal, middle and proximal regions of the secretory portion of Formicidae and Vespidae glands presented a lattice optical pattern. We found a different pattern in the middle secretory portion of the Meliponini, with a zigzag rather than a lattice pattern. This indicates that the biopolymer fibers begin their macromolecular reorganization at this glandular region, different from the Formicidae and the Vespidae, in which the zigzag optical pattern was only found at the lateral duct. Probably, the mechanism of silk production in the Hymenoptera is a characteristic inherited from a common ancestor of Vespoidea and Sphecoidea; the alterations in the pattern observed in the Meliponini could be a derived characteristic in the Hymenoptera. We found no similarity in the macromolecular reorganization patterns of the silk between the Hymenoptera species and the silkworm.
Keywords: Ant; Bee; Larval salivary glands; Polarized-light microscopy; Silk; Silk gland; Silkworm; Wasp; polymer; protein; animal tissue; anisotropy; ant; controlled study; fiber; formicidae; Hymenoptera; inheritance; larva; Lepidoptera; macromolecule; microscopy; nonhuman; polarization; protein structure; salivary gland; secretion; silk; silkworm; species comparison; sphecoidea; Vespidae; wasp; Animals; Ants; Bees; Bombyx; Larva; Microscopy, Polarization; Photomicrography; Salivary Glands; Wasps; Animalia; Apoidea; Bombyx mori; Formicidae; Hexapoda; Meliponinae; Sphecoidea; Vespoidea